1989
DOI: 10.1177/001872088903100501
|View full text |Cite
|
Sign up to set email alerts
|

Component Fluency in a Problem-Solving Context

Abstract: Theories of cognitive skill suggest two hypotheses about component task practice. First, component practice increases the speed of executing component skills during problem solving. Second, component practice produces component skills that behave as encapsulated subroutines. Eight college students practiced making judgments about digital logic gates for 1360 trials. At two points during practice, they solved circuit problems that did or did not require logic gate knowledge. Time per move declined with problem-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…This led to better appreciation of the meaningful context (i.e., availability of supportive information) during practice. Research by Carlson and colleagues (Carlson, Sullivan and Schneider 1989;Carlson, Khoo and Elliott II 1990) emphasizes the beneficial influence of a meaningful context during practice of procedural information presented earlier. They found that transfer test scores increased when learners were able to practice the procedural information in meaningful contexts.…”
Section: Discussionmentioning
confidence: 99%
“…This led to better appreciation of the meaningful context (i.e., availability of supportive information) during practice. Research by Carlson and colleagues (Carlson, Sullivan and Schneider 1989;Carlson, Khoo and Elliott II 1990) emphasizes the beneficial influence of a meaningful context during practice of procedural information presented earlier. They found that transfer test scores increased when learners were able to practice the procedural information in meaningful contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Basically, tasks within and between domains are assumed to differ with respect to the composition of demands that necessarily require controlled processing and those that can pass into automatic processing (Schneider, & Fisk, 1983). Similarly, for a particular task, indi viduals are assumed to differ in the extent to which the taskspecific information-processing elements that can be automatized are actually automatized (e.g., Carlson, Sullivan, & Schneider, 1989). In the following two sections, we describe in detail how automatic and controlled processes may interact in the two do mains considered, reading and problem solving.…”
Section: Time On Task Effects and Dual Processing Theorymentioning
confidence: 99%
“…For example, after learners practice how to search relevant literature, the instructor may provide them with part-task practice on using Boolean operators, so as to help learners achieve automaticity of that skill (cf. Carlson et al 1989). …”
Section: Part-task Practicementioning
confidence: 99%
“…By most definitions, complex cognitive skills consist of many constituent skills, each of which must be performed in a coordinated and integrated fashion using high-level schemas or organizing strategies, and at least some of which involve conscious processing, such as decision making, problem-solving, or reasoning (Carlson et al 1989;Gopher et al 1989;Peck and Detweiler 2000; van Merriënboer 1997). Therefore, recent instructional theories tend to focus on authentic and whole learning tasks that require learners to address real-world problems as the driving force for transfer of learning (Merrill 2002(Merrill , 2007; van Merriënboer and Kirschner 2001).…”
Section: Introductionmentioning
confidence: 99%